A mixture theory based method for three-dimensional modeling of reinforce concrete members with embedded crack finite elements - Manzoli, O. L. [UNESP]; Oliver, J.; Huespe, A. E.; Diaz, G. (Techno-press, 2008)
The paper presents a methodology to model three-dimensional reinforced concrete members by means of embedded discontinuity elements based on the Continuum Strong Discontinuous Approach (CSDA). Mixture theory concepts are used to model reinforced concrete as a 31) composite material constituted of concrete with long fibers (rebars) bundles oriented in different directions embedded in it. The effects of the rebars are modeled by phenomenological constitutive models devised to reproduce the axial non-linear behavior, as well as the bond-slip and dowel action. The paper presents the constitutive models assumed for the components and the compatibility conditions chosen to constitute the composite. Numerical analyses of existing experimental reinforced concrete members are presented, illustrating the applicability of the proposed methodology.
Keywords: finite elements; fracture mechanics; strong discontinuities; mixture theory; finite elements with embedded discontinuities